Factors Influencing the Timing of the First HIV Virological Test for HIV Exposed Infants; A Cross Sectional Descriptive Study of HIV Positive Breastfeeding Mothers and their Infants in 10 Selected High-Volume Health Facilities in a Rural District in Western Uganda (Global Journal of Medical Research, 2020)
Introduction: Although Option-B plus has registered tremendous success in the Prevention of Mother to Child Transmission (PMTCT) of HIV, the failure to follow the HIV testing algorithm for HIV Exposed Infants (HEIs) after birth is likely to make achieving zero new HIV infections among children unrealistic. Due to this, we sought to determine the factors affecting uptake of first Polymerase Chain Reaction (PCR) test among HEIs to inform the selection of strategies to strengthen Early Infant Diagnosis (EID), an indicator that tracks progress towards achieving zero new HIV infections in children.
Keywords: HIV virological test; PCR HIV test; HIV exposed; infants; western uganda